Use of polymer modified binders as rejuvenators in recycled asphalt mixtures - Torres, Hélder P. (2020)
Road paving recycling has been acquiring more relevance in society, especially within the paradigm of a circular economy. The addition of waste materials in asphalt mixtures is an excellent solution to face the gradual emergence of a great diversity of waste materials and reduce the production costs. This study aims to evaluate the addition of commercial and laboratory-produced polymer modified binders as rejuvenators in recycled asphalt mixtures with high contents of reclaimed asphalt pavement material (RAP). A commercial polymer modified binder (PMB) and a conventional bitumen modified with 5% of styrene-butadiene-styrene (SBS) or 4% of Regefalt were added to RAP aged bitumen and compared with a rejuvenated binder. Fatigue, permanent deformation and water sensitivity tests carried out on recycled mixtures produced with those binders showed that polymer modified binders could be used as rejuvenators to improve their performance significantly. The recycled asphalt mixture produced with the commercial PMB presented the best mechanical performance. The polymer-modified binders revealed an ageing resistance equivalent to that of the control rejuvenated binder, or slightly better in the case of the final binder with SBS polymer.